Davy Takes to the Hills: Dialogic Enquiry and the Aesthetics of the Prospect View. (3rd July 2019) - Fulford, Tim
Abstract : I discuss some of the versions of scientific enquiry used and promoted by Davy, arguing that his self-fashioning as a "genius" and "hero of science" in the years 1801–1820, paralleling the self-fashioning of his friend Wordsworth, created a public persona that tended to occlude a practice of group enquiry to which, however, he publicly returned in his last years – significantly revising it so that it became a dialogic form of writing. This form, I suggest, construed knowledge not as the production of facts – or elements – by inductive method and controlled experiment, but as a conversational process between trusted peers, in which it is not just possible but fundamental to express doubt. Requiring no absolute commitment to a single view, dialogic exploration embraced uncertainty to engender new questions and ambivalence to generate new modes of enquiry.